Altered perspective-dependent brain activation while viewing hands and associated imitation difficulties in individuals with autism spectrum disorder - Okamoto, Yuko (2018)
Background: Individuals with autism spectrum disorder (ASD) appear to have a unique awareness of their own body, which may be associated with difficulties of gestural interaction. In typically developing (TD) individuals, the perception of body parts is processed in various brain regions. For instance, activation of the lateral occipito-temporal cortex (LOTC) is known to depend on perspective (i.e., first- or third-person perspective) and identity (i.e., own vs. another person's body). In the present study, we examined how perspective and identity affect brain activation in individuals with ASD, and how perspective- and identity-dependent brain activation is associated with gestural imitation abilities. Methods: Eighteen young adults with ASD and 18 TD individuals participated in an fMRI study in which the participants observed their own or another person's hands from the first- and third-person perspectives. We examined whether the brain activation associated with perspective and identity was altered in individuals with ASD. Furthermore, we identified the brain regions the activity of which correlated with gestural imitation difficulties in individuals with ASD. Results: In the TD group, the left LOTC was more strongly activated by viewing a hand from the third-person perspective compared with the first-person perspective. This perspective effect in the left LOTC was significantly attenuated in the ASD group. We also observed significant group differences in the perspective effect in the medial prefrontal cortex (mPFC). Correlation analysis revealed that the perspective effect in the inferior parietal lobule (IPL) and cerebellum was associated with the gestural imitation ability in individuals with ASD. Conclusions: Our study suggests that atypical visual self-body recognition in individuals with ASD is associated with an altered perspective effect in the LOTC and mPFC, which are thought to be involved in the physical and core selves, respectively. Furthermore, the gestural imitation difficulty in individuals with ASD might be associated with the altered activation in the IPL and cerebellum, but not in the LOTC. These findings shed light on common and divergent neural mechanisms underlying atypical visual self-body awareness and gestural interaction in ASD.